Garis Batas Antara Agama dan Budaya Dalam Perspektif Antropologi (Jurnal Adabiya, 2020)
This paper discusses the boundary line between culture and religion, especially in connection to Is-lam. From an anthropological perspective, religion is regarded as one element of universal elements of culture.Religion is sacral, while culture is profane. In addition, Islam is not a cultural religion, it comes from Allah,the Almighty God. Therefore, the issue of the boundary between culture and religion is important to discuss.Through the searching of each characteristic, the boundary line between culture and religion could be found.
Keywords: Culture; religion; anthropology